The Effect of Leadership Style, Motivation, and Competence on The Performance of Functional Civil Servants Managing The Procurement of Goods and Services at The Ministry of Environment/Environmental Control Agency - Resa Gumilang; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2025)
This study aims to empirically analyze the influence of leadership style, work motivation, and competence on the performance of civil servants (ASN) in functional positions responsible for goods and services procurement within the Ministry of Environment/Environmental Control Agency (KLH/BPLH). The main issue addressed in this research is the variation in ASN performance in procurement management, which affects the effectiveness, efficiency, and accountability of public service delivery. The study employs a quantitative approach with a correlational–verificative design, involving 30 ASN as respondents through a saturated sampling technique, in which the entire population was used as the research sample. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed through multiple linear regression using IBM SPSS Statistics version 26. The results reveal that leadership style, work motivation, and competence have a positive and significant effect on ASN performance, both partially and simultaneously. The coefficient of determination (R² = 0.692) indicates that 69.2% of the variation in ASN performance is explained by the three independent variables, with competence being the most dominant factor. These findings suggest that an inspirational leadership style, high work motivation, and adequate professional competence are key determinants in improving the performance of public procurement personnel. Theoretically, this study reinforces the principles of transformational leadership theory and competency-based performance theory within public sector management. Practically, it recommends strengthening ASN development policies through participatory leadership training, performance-based motivation systems, and technical procurement certification programs. The findings contribute to enhancing human resource governance and developing sustainable strategies for improving public servant performance in Indonesia’s bureaucratic institutions.